Liposarcoma of the Nasopharynx: Diagnosis and Management of a Rare Diagnostic Entity - George X. Papacharalampous; Dimitrios Kikidis; Alexios Vasileiou; Aggeliki Bousiotou; Aristeidis Chrysovergis (Case Reports in Medicine)
Liposarcoma is one of the most frequently occurring soft tissue sarcomas in adulthood. The majority of liposarcomas arise in the lower extremities and retroperitoneum, while the incidence of this tumor in the head and neck region is reported to be extremely low, comprising 1.8%–6.2% of all cases. Nasopharyngeal liposarcoma is exceptionally rare, with only three cases having been reported in the English literature. This paper presents a case of a nasopharyngeal liposarcoma, treated with endoscopic tumor debulking, followed by adjuvant chemotherapy and radiotherapy, and reviews the current literature with regard to diagnosis and management of such lesions. Most authors agree that the imaging modality of choice is magnetic resonance imaging. Although radiographic findings usually support diagnosis, the imaging characteristics of such lesions may considerably vary, depending on the histological subtype and the macroscopic appearance of the tumor. The treatment of choice is complete surgical excision when possible. Although the role of postoperative radiotherapy is not clearly defined, some authors support that radiotherapy might delay or prevent local recurrence. However, there is no adequate evidence that the combination of surgery and radiotherapy lowers the possibility of distant metastasis of the head and neck liposarcomas. The role of adjuvant or neoadjuvant chemotherapy still remains controversial.